Computer networking : an all-in-one beginner's guide to understanding communications systems, network security, internet connections, cybersecurity and hacking - Kiser, Quinn ([USA] : [publisher not identified], 2020)
This book delivers a variety of computer networking-related topics to be easily understood by beginners. It focuses on enabling you to create a strong foundation of concepts of some of the most popular topics in this area. Typically, you may have had to purchase several books to cover the majority of the topics provided in this book. However, we have concentrated all five popular topics into one book for beginners. That is why we have called the book an all-in-one guide. We have provided the reader with a one-stop highway to learning about the fundamentals of computer networking, Internet connectivity, cybersecurity, and hacking.
Introduction -- Chapter 1. Computer Networking Basics -- Chapter 2. Networking Services Explained -- Chapter 3. Getting into the Networking Hardware fundamentals of computer relationships -- Chapter 4. Wireless communication systems and connecting to the internet -- Chapter 5. Common Network protocols and Ports -- Chapter 6. Learning about the OSI Networking model -- Chapter 7. Network Security, Cybersecurity, and hacking methods -- Chapter 8. Useful Cybersecurity Tips for 2020 -- Conclusion.
Keywords: COMPUTER NETWORK